Meningkatkan Hasil Belajar Siswa Dengan Pendekatan Model Pembelajaran Student Teams Achievement Division (STAD) - Nur Hakim (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The purpose of this study was to improve thematic learning out comes ecpeciallyon theme 6 Cita-citaku Subtema 2 Hebatnya Cita-citaku using learning methods Student Teams Achievement Division (STAD. This type of researc is (class action research) consiting of three cycles in which each cycle is carred out in four stages. These stage include planning, implementing action, observing, and reflecting. The subjects in this study were study students IV MI Nurul Huda Sawo Dukun Gresis as many as 33 students consisting of 18 female students and 15 female students. Data collection techniques used in research are observation, test and interviews. The collected data was analyzed by qualitatif data analysis and quantitative data analysis techniques and analysis of the tests. The results of the study show, in the pre test stage the oyer all students get relatively low learning out come, which is an average of 61.12 with a percentage of learning completeness of 42.42% , In cycle I the application of learning method Student Teams Achievement Division (STAD) was carried out, and in the firs cycle was also given a learning test in the form of post test I where the average learning out comes obtained in the first cycle are 69.91 with the percentage of learning completeness of 57.57% in the cycle the student learning out comes obtained by students are quite sufficient. In the cycle II the learning out come obtained by students are classified as good. Where the average obtained is 77 with the percentage of learning comlpeteness of 87.87%%. Were as, in the last cycle III of learning out comes obtained by cycle is student learning out comes experienced a drastic increase wich can be seen a from the average test given. Students get an average on the test cycle III of 83.30 with a percentage of learning completeness of 96.96%.The consclusion that the learning out come of thematic are theme 6 Cita-citaku Subtema 2 Hebatnya Cita-citaku for student in the class IV MI Nurul Huda Sawo Dukun Gresik. Through learning methods Student Teams Achievement Division (STAD) have increased.